Undocumented latina immigrants in Orange County, California : a comparative analysis - Chavez, L.; Hubbell, F. a.; Mishra, S. I.; Valdez, R. B.; Chavez, L.; Hubbell, F. a.; Mishra, S. I.; Valdez, R. B.
tbls.
Keywords: Inmigrantes; Estados Unidos de America; California; Mujeres; Latinoamericanos; Mercado de Trabajo